Improvement of Land Relations in the Context of Sustainable Development of Rural Areas in Ukraine - SHARAPOVA, Svitlana; LISOVA, Tetiana; BREDIKHINA, Viktoriya; LIALIUK, Olexii (Journal of Environmental Management and Tourism, 2021)
Ensuring the sustainable development of agricultural production, in particular by legal means, becomes especially important for both Ukraine and other countries. The article considers the legal framework aimed at ensuring the effective conduct of modern agricultural production. Proposals for improving land and agrarian legislation in this area have been developed. In particular, it is proposed to develop a standard model of sustainable development of rural areas and the adoption of the Law of Ukraine “On sustainable development of rural areas”. It should contain criteria for distinguishing the production, social and environmental components of sustainable development of rural areas, in particular, enshrine their definitions, contain special rules and regulations in separate sections. From the analysis of the provisions of national and European legal documents and the situation that exists within rural areas, the conclusion is made that it is expedient to introduce into the practice of agrarian legislation compliance with the principles accompanying the process of sustainable development of rural areas, namely: clear demarcation basic concepts and principles of conducting activities in rural areas, market orientation, balance, adaptability of rural development, taking into account regional features of rural development, local partnership, isolation, quality priority.